Supplementation of vitamin C as anti heat-stress agen of broilers - Kusnadi, Engkus (Indonesian Animal Sciences Society, 2006)
High environmental temperatures may cause heat stress in poultry. This may increase water consumption, decrease feed consumption and in turn, decrease production level.Â This experiment was conducted to study the supplementation of vitamin C as anti heat-stress agent of broilers. In this research, were used 72 broilers 21 days old. The treatment are two kinds. The first, two poultry house temperatures (32 and 240C as warm temperature and cool temperature respectively) and second, four levels suplementation of vitamin C (0, 250, 500 and 750 ppm of ration as C0, C250, C500 and C750 respectively). Variables measured are feed consumption, body weigh gain, content of abdominal lipid and feed convertion. The data collected were analized with a split plot design in completelly random design and continued with the contrast-orthogonal test when significantly different The result indicated that vitamin C significantly (P<0.05) increased feed consumption and body weigh gain. The warm temperature significantly (P<0.05) decreased feed consumption and body weigh gain. Feed convertion of C250, C500 and C750 in warm temperature were significantly (P<0.05) lower than C0. The supplementation of 250 ppm vitamin C (C250) was most efective as anti heat-stress agent in broilers kept at warm temperature. Key Words: Vitamin C, Broiler, Heat-Stress